2009
DOI: 10.1158/0008-5472.can-09-0389
|View full text |Cite
|
Sign up to set email alerts
|

When the Sphingosine Kinase 1/Sphingosine 1-Phosphate Pathway Meets Hypoxia Signaling: New Targets for Cancer Therapy

Abstract: The reduction in the normal level of tissue oxygen tension or hypoxia is a characteristic of solid tumors that triggers the activation of signaling pathways promoting neovascularization, metastasis, increased tumor growth, and resistance to treatments. The activation of the transcription factor hypoxiainducible factor 1A (HIF-1A) has been identified as the master mechanism of adaptation to hypoxia. In a recent study, we identified the sphingosine kinase 1/sphingosine 1-phosphate (SphK1/S1P) pathway, which elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 33 publications
4
51
1
2
Order By: Relevance
“…45 Interestingly, SK1 was recently shown to enhance hypoxiainducible factor-1a stability and function. 46,47 Notably, this is consistent with another study that demonstrated that S1P increases hypoxia-inducible factor-1a protein stability through activation of the S1P 2 receptor, 48 suggesting that SK1/S1P may increase TFR1 transcription through the accumulation of hypoxiainducible factor-1a. Clearly, further studies are required to investigate these possibilities.…”
Section: Discussionsupporting
confidence: 89%
“…45 Interestingly, SK1 was recently shown to enhance hypoxiainducible factor-1a stability and function. 46,47 Notably, this is consistent with another study that demonstrated that S1P increases hypoxia-inducible factor-1a protein stability through activation of the S1P 2 receptor, 48 suggesting that SK1/S1P may increase TFR1 transcription through the accumulation of hypoxiainducible factor-1a. Clearly, further studies are required to investigate these possibilities.…”
Section: Discussionsupporting
confidence: 89%
“…To explore the mechanisms underlying the resistence effects of SphK1, we tested the effect of SphK1 on the AKT/GSK3β pathways, which have been demonstrated to be involved in tumor progression (24). We have demonstrated in the present study that p-Akt and p-GSK3β was downregulated in SphK1-knocked down HCC cells, suggested Akt/GSK3β activation through SphK1 signaling is associated with oxaliplatin resistance in HCC cells.…”
Section: Discussionmentioning
confidence: 52%
“…Overexpression of SphK1 may confer the development of resistance to chemotherapeutics, whereas disruption of SphK1/S1P signaling may restore or improve chemotherapy sensitivity (24). For example, raised SphK1 has been associated with chronic myeloid leukemia resistance to imatinib and pancreatic cancer cell resistance to gemcitabine (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Although both subtypes catalyze the same reaction, it remains unclear whether they have overlapping or diverging cellular functions [5]. Accumulating evidence now suggests a key role for SK-1 in cell proliferation and migration implicating a role of this subtype in tumour growth and metastasis formation [4][5][6][7]. Additionally, the overexpression of SK-1 in mouse fibroblasts leads to foci formation in soft agar thus, suggesting that the SPHK1 gene may act as an oncogene [8].…”
Section: Introductionmentioning
confidence: 99%